The Production of Antibiotics Must Be Reoriented: Repositioning Old Narrow-Spectrum Antibiotics, Developing New Microbiome-Sparing Antibiotics - Sylvain Diamantis; Nicolas Retur; Benjamin Bertrand; Florence Lieutier-Colas; Philippe Carenco; Véronique Mondain; on behalf of PROMISE Professional Community Network on Antimicrobial Resistance (MDPI AG, 2022)
The development of broad-spectrum antibiotics to control multidrug-resistant bacteria is an outdated business model. This strategy has led to the introduction of highly effective antibiotics, but their widespread use has contributed to the emergence of even broader antibiotic resistance. In a strategy to combat antimicrobial resistance, we believe that the use of narrow-spectrum antibiotics should be promoted. This should involve both the repositioning of old antibiotics and the reorientation of research and development towards new narrow-spectrum antibiotics with a low ecological impact. These antibiotics could be prescribed for common conditions such as sore throats and cystitis, which account for the bulk of antibiotic use in humans. Narrow-spectrum, targeted, microbiome-sparing antibiotics could help control antibiotic resistance while being economically sustainable. Their development and production should be supported by governments, which would ultimately benefit from reduced health care costs.